Production and Evaluation of the Physiochemical and Sensory Property of Biscuits From Wheat-Maize-Cashewnut Flour Blends - Mshelia, L. P.; Ndahi, T. E.; Peter, D.; Danladi, U.; Kasum, A. L.; Badau, M. H. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This study aimed to prepare and evaluate the quality characteristics of biscuits produced from wheat, maize and cashew nut flour blends. The flours were processed and blended using different proportions of eight (8) formulations with whole wheat flour as a control. The proximate composition of the flour blends, physical properties and sensory evaluation of the biscuits produced were determined using the standard analytical techniques. The data obtained were statistically analyzed using Analysis of Variance (ANOVA). The results show that moisture, ash, fat, protein and carbohydrate of the flours used for the blends ranged from 5.43-10.12 %, 1.74- 29.51, 9.34-26.56 and 34.48-77.25% respectively. Also, the moisture, ash, protein, fat, fibre carbohydrate and energy values of the biscuit ranged from 2.90 -3.92%, 0.99 - 1.57%, 11.19 - 14.59%, 16.24 - 20.30%, 0.97 - 4.85%, 56.04 - 66.96% and 457.68 - 470.80 Kcal/100g respectively. However, with an increase in maize flour (Mf), a significant increase in fibre contents was observed while moisture content decreased drastically. Additionally, the protein, fat and energy contents of supplemented samples were found to be higher than the control but decreased with an increase in maize flour levels. The weight, length, width, thickness and spread ratio of the biscuit samples differed significantly (p<0.05) ranging from 15.25 - 17.36g, 51.70 - 53.03mm, 50.54 - 52.36mm, 9.57 - 11.27mm and 4.48 - 5.47mm respectively. The spread ratio and overall acceptability of biscuit samples decreased with the increased level of maize flour although the sensory evaluation showed that most values obtained are closer to the control. This shows that the acceptance level of the biscuits samples was higher except for sample Wmc 8 ( sample produced from wheat, maize and cashew nut flour at the ratio of 20:70:10). In conclusion, the production of biscuits supplemented with cashew nuts and maize flour increased protein, energy contents and taste, which could be used to address protein-energy malnutrition prevalence.